Viral and cellular interactions during adenovirus DNA replication. Issue 24 (17th December 2019) - Charman, Matthew; Herrmann, Christin; Weitzman, Matthew D.
Abstract : Adenoviruses represent ubiquitous and clinically significant human pathogens, gene‐delivery vectors, and oncolytic agents. The study of adenovirus‐infected cells has long been used as an excellent model to investigate fundamental aspects of both DNA virus infection and cellular biology. While many key details supporting a well‐established model of adenovirus replication have been elucidated over a period spanning several decades, more recent findings suggest that we have only started to appreciate the complex interplay between viral genome replication and cellular processes. Here, we present a concise overview of adenovirus DNA replication, including the biochemical process of replication, the spatial organization of replication within the host cell nucleus, and insights into the complex plethora of virus–host interactions that influence viral genome replication. Finally, we identify emerging areas of research relating to the replication of adenovirus genomes. Abstract :